PERJANJIAN INTERNASIONAL PADA HIERARKI PERATURAN PERUNDANG-UNDANGAN: PERBANDINGAN DI INDONESIA DENGAN PRANCIS - Cahayarizputra, Albiruwahidhan (Uti Possidetis: Journal of International Law, 2025)
This paper is intended to discover the comparison between the role of international treaties in the hierarchy of legislations in Indonesia and France. Normative legal research is used in this paper with a comparative approach to find the similarities and differences between the legal systems in Indonesia and France, and also to find possible solutions to overcome current legal problems in Indonesia. The result of this paper is that the position of international treaties in Indonesia’s legal hierarchical order is largely unclear. The ratification of treaties in Indonesian law can be in form of regular laws (undang-undang) or presidential regulations (peraturan presiden). Meanwhile, France places international treaties in higher hiearchical position compared to ordinary laws, but lower postion compared to the Constitution, although France allows for constitutional amendments to accomodate international treaties that are found unconstitutional by the Constitutional Council. The unclear position of international treaties in Indonesia’s hierarchy of laws potentially causes problems if domestic laws conflict with the provisions of international treaties. International law mainly views that any conflict with domestic regulations is not an excuse to shirk their obligations to fulfill the provisions of a treaty, unless said treaty conflicts with the basic norms of a country. In order to guarantee the principles of pacta sunt servanda, and to ensure the harmonization of international agreements with national laws, thus international treaties should be given specific position in the hierarchy of laws.